AF-CARE: The current approach in atrial fibrillation management - Rizal, Ardian (Heart Science Journal, 2025)
Despite improvements in treatment, atrial fibrillation (AF) continues to pose a serious threat to global health, with increasing rates of morbidity and mortality. By endorsing the AF-CARE approach, the 2024 ESC guidelines shift the paradigm from the conventional "CC to ABC" model and place more emphasis on patient empowerment, comorbidity management, and rhythm control. Important changes include promoting early catheter ablation for certain patients, as shown by the CABANA and EARLY-AF trials, and prioritising risk factor modification (such as obesity and sleep apnoea) as a therapeutic approach, backed by trials like LEGACY. The guidelines also emphasise patient-centred care, incorporating digital tools and education. The paradigm shift towards holistic AF management is highlighted in this editorial, which combines shared decision-making, lifestyle interventions, and technological innovation to enhance results.